A Central African Perspective on Delegated Protected Area Management. (September 2018) - Scholte, Paul; Agnangoye, Jean-Pierre; Chardonnet, Bertrand; Eloma, Henri-Paul; Nchoutpouen, Chouaibou; Ngoga, Telesphore
In recent years, there has been a trend for African states to delegate protected area management to private partners. Central Africa is confronted with rapidly declining wildlife populations, with scarce funding and poor incentives as root causes. This raises the question as to whether management delegation can counter this trend. However, our understanding of the efficiency of such partnerships and how they need to be handled is poor. Based on hands-on experiences and external evaluations, we developed best practices of delegated management partnerships in Central Africa. This triggered the development of the here presented Central African perspective, enriching a debate that is biased toward other parts of the continent and dominated by private conservation partners. In particular, we emphasize that in Central Africa, (a) protected areas with delegated management are among the most prestigious ones, albeit with serious management challenges; (b) it is the importance of the protected area that justifies its inclusion in formal development cooperation agreements—the dominant source of funding; (c) lack of legal provisions has been an obstacle to initiate delegated management partnerships for some countries and its wider use in others; (d) increasingly, foundations are being created as implementing national entities; and (e) raising national capacities in handling delegated management should be at the forefront of partnerships. We conclude by highlighting the importance of the new regional best practices that are based on the four stages: identification, preparation, negotiation, and implementation, of which the first three have often been neglected by Central African governments.